IMAHO (INDONESIA MALAYSIA IN HARMONY): STRATEGI CERDAS ALA MAHASISWA KESEHATAN DALAM MEMBANGUN KERUKUNAN RUMPUN MALAYA - Ambalavanan, Darshainy; Yee, Ng Mun; Arrazy, Nauval; Sugiyanto, Raisatun Nisa (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2013)
Indonesia and Malaysia relationship as two neighbouring countries often face bilateral problems, for example cultural, political, and social conflicts. Some solutions for those conflicts had already been strived by both countries, but the solution does not settle the problem down to the community, thus negative sentiments about Indonesia-Malaysia relationship is prevalent in the community. IMAHO is a new solution brought by Indonesian and Malaysian medical students in assistance by universities and governments from both countries in order to eliminate negative sentiments by means of activities carried out by collaboration of Indonesian and Malaysian students. All activities in the community are expected to be an example for the society to live in harmony and negative sentiments about Indonesia-Malaysia relationship can be eliminated.